The Use of Code Switching Found in Podcast Ruang Sandi by Sandiaga And Cinta Laura - Ni Made Verayanti Utami; Ida Ayu Putri Gita Ardiantari; Sri Cahyani, Ni Putu Sukma (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
The study concern with the use of code switching found in Podcast Ruang Sandi YouTube channel by Sandiaga Uno and Cinta Laura. This study aims to investigate the types and the reasons of code switching found in the podcast. The data in the study were analyzed by applying descriptive qualitative method based on the theory of Hoffman (1991) in solving the first problem, and theory from Grosjean (1982) to solve the second problem which also supported by using the theory of Gumperz (1982) regarding speech function of code switching. Based on the result of the findings, inter-sentential switches appeared as the most dominant occurrence, because Sandiaga Uno and Cinta Laura feel easier and more comfortable to convey their message in full sentence in English. Meanwhile, regarding the reasons of code switching, fill a linguistics need lexical item, set phrase, discourse maker or sentence filler came out as dominant reasons, because they cannot find the appropriate words and also the foreign elements are more understood by the viewers of Podcast Ruang Sandi.